Comparison of Primer Types to Produce Fungal DNA Fragment from Garlic Plant Root Samples - Dewi, Fibrianti Shinta; Abadi, Abdul Latief; Syib'li, Muhammad Akhid (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2023)
Fusarium wilt disease caused by Fusarium oxysporum f.sp cepae is a widespread and dangerous diseases in garlic commodities. The combination of AMF and Bacillus amyloliquefaciens can be an effective solution to reduce losses due to attacks by these pathogens. The PCR technique is initial method that has proven to be significant in detecting fungal target DNA so that the effectiveness of biological agents can be determined. The aim of this study is to compare the types of primers that are effective for use in detecting fungal groups in PCR. This research was conducted in October 2023 - November 2024. The types of primers compared were ITS1-F/ITS4-R and LSU200A-F/LSU476-R with spectophotometry and fluometry quantification. The results show that ITS1-F/ITS4-R forms DNA band with a size of 700 bp, while LSU200A-F/LSU476-R had a size of 290-300 bp. The electropherogram also showed differences in DNA distribution which confirmed the results on agarose more specifically in the range 19-12,999 bp. In general, these results prove that the two types of primers have different abilities in fragmenting target DNA. This knowledge can help in detecting DNA at an early stage which can be used in various analyzes that can help in integrated plant disease management.